2016
DOI: 10.1080/17421772.2016.1126674
|View full text |Cite
|
Sign up to set email alerts
|

The Causes of Urban Sprawl in Spanish Urban Areas: A Spatial Approach

Abstract: Acknowledgments: We would like to thank the participants in the 55th European Regional Science Association and the 89th Western Economic Association International conferences and three anonymous referees for their valuable comments and suggestions. Miguel Gmez-Antonio acknowledges financial support from the ECO2012-36032-C03-01 research funding and Stuart Sweeney acknowledges support from National Science Foundation award BCS-0454993.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 85 publications
0
25
0
2
Order By: Relevance
“…If a municipality entails significant growth of population and buildings, it is advisable to set, through institutional frameworks (e.g., territorial plan, regulatory plan), nonexceedable limits for territorial development [69]. Municipalities do not resort to significant limits in the early stages of suburbanisation, because they often compete with other municipalities for new inhabitants [26], and so many municipalities do not make any significant regulation until the capacity of the municipality is fulfilled. However, the interest of developers, as well as individuals, in land and real estate in the municipality can predict in the future a higher degree of development dynamics and pressure on a municipality [68], and thus, it is possible to predefine institutional frameworks and control mechanisms in the municipality development [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a municipality entails significant growth of population and buildings, it is advisable to set, through institutional frameworks (e.g., territorial plan, regulatory plan), nonexceedable limits for territorial development [69]. Municipalities do not resort to significant limits in the early stages of suburbanisation, because they often compete with other municipalities for new inhabitants [26], and so many municipalities do not make any significant regulation until the capacity of the municipality is fulfilled. However, the interest of developers, as well as individuals, in land and real estate in the municipality can predict in the future a higher degree of development dynamics and pressure on a municipality [68], and thus, it is possible to predefine institutional frameworks and control mechanisms in the municipality development [16].…”
Section: Discussionmentioning
confidence: 99%
“…In the OECD countries between 2001 and 2011, the trend of the decentralisation of population prevails in the analysis of mechanical population movements within functional urban areas, with population growth not taking place directly in existing cores but usually in their immediate vicinity, in places with low population densities [23], while such residents do not have to be from the core city, but also from other cities [24,25]. In addition, if there are more municipalities in the immediate background of the city, their spatial interaction in terms of expansion may occur within neighbouring municipalities, as individual municipalities are competing for new inhabitants, thus significantly promoting the growth of the core city [26]. In the suburbanisation process, residential populations are very often increasing at the periphery of cities, but the increase in new jobs in these areas is generally not the same, and thus, strategies based on polycentric development very often fail [27].…”
Section: Suburbanisation In the Context Of Environmental Aspects And mentioning
confidence: 99%
“…More recent studies apply sophisticated spatial regression analyses and expand the model to make it more suitable for polycentric metropolitan regions (e.g. Go´mez-Antonio et al, 2016). Many of these studies have confirmed that the assumptions of the model -namely that urban area is a function of population, income, land values and marginal transportation costs -have held up under a wide variety of model specifications.…”
Section: Introductionmentioning
confidence: 98%
“…As research shows, the available technical infrastructure is of great importance, as well as the form of spatial structure development resulting, among others, from the demand for residential or industrial areas [67,68]. Gomez-Antonio and Hortas-Rico [2014] prove that urban sprawl is taking place in Spain [69]. They also indicate that the emergence of urban sprawl in the communes surrounding the city intensifies when sprawl occurs in a neighboring commune.…”
Section: Instruments For Influencing Urban Sprawlmentioning
confidence: 99%